2020
DOI: 10.1097/aln.0000000000003557
|View full text |Cite
|
Sign up to set email alerts
|

Hypotension Prediction Index for Prevention of Hypotension during Moderate- to High-risk Noncardiac Surgery

Abstract: Background The Hypotension Prediction Index is a commercially available algorithm, based on arterial waveform features, that predicts hypotension defined as mean arterial pressure less than 65 mmHg for at least 1 min. We therefore tested the primary hypothesis that index guidance reduces the duration and severity of hypotension during noncardiac surgery. Methods We enrolled adults having moderate- or high-risk noncardiac surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
107
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(121 citation statements)
references
References 18 publications
7
107
6
1
Order By: Relevance
“…In contrast to the studies mentioned and our data, a recent study by Maheshwari et al 29 demonstrated no significant difference comparing a HPI‐guided group to an unguided group. They reported a time‐weighted average of 0.14 mmHg and a time‐weighted mean arterial pressure >83 mmHg (84.9 vs. 83.4 mmHg, p = 0.193) in both groups.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the studies mentioned and our data, a recent study by Maheshwari et al 29 demonstrated no significant difference comparing a HPI‐guided group to an unguided group. They reported a time‐weighted average of 0.14 mmHg and a time‐weighted mean arterial pressure >83 mmHg (84.9 vs. 83.4 mmHg, p = 0.193) in both groups.…”
Section: Discussioncontrasting
confidence: 99%
“…The time-weighted average of hypotension seems a very promising variable to evaluate the degree of intraoperative hypotension, taking into account both the severity of hypotension and its duration as well as the total surgical time. In this regards, our intervention group found similar values of time-weighted average (0.12 mmHg) as compared to other larger studies (0.10 mmHg [10] and 0.14 mmHg [12]).…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, our results seem in line with most of currently published ndings. Although a recent study by Maheshwari et al conducted in 214 patients undergoing non-cardiac surgery questioned the role of HPI [12], most of the published evidence supports the value of HPI in predicting hypotension. Indeed, such results have been found in patients undergoing total hip arthroplasty [13], major/general surgery [14,15] and cardiac surgery [16].…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this, repeated re-assessment of risk after early ARRC treatment may be able to identify the 50% of moderate-risk patients who were unlikely to develop major adverse events overnight 27 . Considering the high incidence of hypotension in this study, there may be a role in this for devices with the capacity to predict hypotension 28 . The potential impact of this can then be estimated prospectively using this model, with costs (to now include device consumables and fewer staff) appropriately adjusted.…”
Section: Discussionmentioning
confidence: 95%